Karacs Teréz pedagógiája. Vallástanítás a miskolci Felsőbb Leánynevelő Intézet-ben - BÁTORINÉ MISÁK, Marianna (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Pedagogy of Teréz Karacs. Teréz Karacs was one of the remarkable pioneers of her age in national female edu-cation, with a unique working ability, steadiness, and power. The Trans-Tisza Re-formed Diocese, specifically the congregation of Miskolc, can also be very thankful to her. The pedagogy of Karacs was not just up to date but beyond her age. She opened the doors of her finishing school under such harsh circumstances and in an age in which others closed their institutions. Inviting the magistracy of the congre-gation, she received many promises for the unperturbed functioning of her school; however, the lack of finances meant a permanent struggle in the maintenance of the girls’ school. She also gave in her notice many times because of the unrealized prom-ises. Teréz Karacs trained hundreds of girls in her consistent, thorough, and practi-cal pedagogic method and prepared them for life. She did all her work with such a conviction that her efforts are not purposeless, serving and advancing her country, nation, and church. The upper finishing school of Miskolc put a great effort in the education of re-ligion, which principally meant the shaping of a virtuous life, the inner piety in the century of rationalism and liberalism. Besides various subjects, religious education and nurture played an important part in the education of the girls in her institute. These tendencies also bore the marks of everyday life of the ecclesiastic life of the country. In spite of the fact that religious education appeared from the first lesson of the beginners, she did not mention it in her work Some Words on the Education of Girls. Negligence or slight of religious education would not even befit the careful work of Teréz Karacs, who meant to educate trustful and cultured women.